ANALISIS ETNOMATEMATIKA PADA MOTIF ULOS RAGI HOTANG BATAK TOBA - Lubis, Hotma Fifia; Audy Sihol Marito Manurung; Prasita Manginar Tesalonika Napitupulu; Friska Ledina Situngkir (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Mathematics is often perceived as an abstract discipline detached from everyday life, whereas many mathematical concepts are naturally embedded in cultural practices. One form of cultural heritage that contains mathematical elements is Ulos Ragi Hotang, a traditional woven cloth of the Batak Toba community that holds strong ceremonial functions and philosophical values. This study aims to identify and analyze the ethnomathematical concepts embedded in the motifs of Ulos Ragi Hotang and to relate them to formal mathematical concepts. The scope of the study focuses on the analysis of patterns, geometric shapes, repetition, symmetry, ratios, and area found in the arrangement of the motifs. A qualitative research method with an ethnographic approach was employed through visual observation of the motifs, documentation studies, and relevant literature review. The collected data were analyzed descriptively to reveal mathematical elements implicitly present in the structure and composition of the motifs. The findings indicate that Ulos Ragi Hotang motifs contain various mathematical concepts, including repeating patterns and sequences, plane figures such as triangles and rhombuses, parallel lines and angles, reflection and translational symmetry, ratios and proportions, as well as the concept of rectangular area. These concepts function not only as aesthetic elements but also represent Batak Toba cultural values such as balance, harmony, strength, and kinship. The study concludes that Ulos Ragi Hotang has strong potential to be utilized as a contextual and meaningful ethnomathematics-based learning resource in mathematics education while supporting the preservation of local cultural heritage. Furthermore, the findings provide implications for the development of culturally responsive teaching materials that connect mathematical concepts with local traditions, thereby enhancing students’ motivation, conceptual understanding, and appreciation of indigenous culture in contemporary mathematics learning.